2000
DOI: 10.1159/000016579
|View full text |Cite
|
Sign up to set email alerts
|

The Fidelity of Mutans Streptococci Transmission and Caries Status Correlate with Breast–Feeding Experience among Chinese Families

Abstract: Our previous study reported that the fidelity of mutans streptococci (MS) transmission from mother to infant was gender– and race–specific within a Birmingham, Ala., population. We hypothesized that fidelity might be a function of postnatal nurturing practices. The purpose of the present study was to investigate those factors that could be correlated with MS transmission among Chinese children whose nurturing histories were known. Forty–eight families with 2– to 3–year–old children were selected from two kinde… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
44
2
12

Year Published

2004
2004
2016
2016

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 67 publications
(64 citation statements)
references
References 25 publications
5
44
2
12
Order By: Relevance
“…respectively, suggesting vertical transmission. This rate was higher than previously reported in several studies, with ranges between 24 and 71% (1,4,8,18,20,21,24). On the other hand, these results are very similar to a longitudinal study of intrafamilial MS ribotypes that showed at least one common S. mutans ribotype among strains recovered from 14 mother-child pairs; among those pairs, 12 pairs (85%) shared the same ribotype; and among eight maternal strains of S. sobrinus ribotyped, six strains (75%) were detected in the child (14).…”
Section: Discussioncontrasting
confidence: 66%
“…respectively, suggesting vertical transmission. This rate was higher than previously reported in several studies, with ranges between 24 and 71% (1,4,8,18,20,21,24). On the other hand, these results are very similar to a longitudinal study of intrafamilial MS ribotypes that showed at least one common S. mutans ribotype among strains recovered from 14 mother-child pairs; among those pairs, 12 pairs (85%) shared the same ribotype; and among eight maternal strains of S. sobrinus ribotyped, six strains (75%) were detected in the child (14).…”
Section: Discussioncontrasting
confidence: 66%
“…This finding is in accordance with the results of the study by Eronat & Eden 5) , who found that most children with rampant caries were breast-fed for longer than 12 months. Li et al 8) also reported that children who were breast-fed more than 9 months were 5 times more likely to have dental caries at 3 years of age than those who had not been breast-fed.…”
Section: Discussionmentioning
confidence: 99%
“…We hypothesize, however, that the association between maternal cariogenic salivary bacteria and child caries might be strongest under contexts entailing close maternal contacts (e.g., breastfeeding, utensil sharing) and weaker under contexts that imply broader potential sources of infection (e.g., daycare attendance, having siblings). For example, greater fidelity of maternal and child MS genotypes was observed among MS-positive children who were breastfed (Li et al, 2000). If observed, such effect measure modification would strengthen the mechanistic evidence inculpating maternal bacterial transfer as a caries determinant among children, representing an area for future study.…”
Section: Discussionmentioning
confidence: 87%